Challenges of THP-AD centrate treatment using partial nitritation-anammox (PN/A) – inhibition, biomass washout, low alkalinity, recalcitrant and more. (15th September 2021) - Cao, Shenbin; Yan, Wangwang; Yu, Lei; Zhang, Liang; Lay, Winson; Zhou, Yan
Highlights: Two-stage PN/A process for THP-AD centrate treatment had a NRR of 0.55 Kg N/m3 3 /d. Inhibition by the centrate can be overcome by acclimation and system optimization. Recalcitrant organics in THP-AD centrate were identified. The centrate reduced the abundance of functional bacteria in PN and anammox reactors. The abundance of denitrifiers was stable with the increased organics loading. Abstract: The centrate produced from a thermal hydrolysis pretreatment coupled anaerobic digestion (THP-AD) system is generally characterized by high concentrations of ammonium and recalcitrant organics. In this study, a cost-effective partial nitritation-anammox (PN/A) process was developed to evaluate the potential challenges in THP-AD centrate treatment. The results show ammonium oxidizing bacteria (AOB) and anammox bacteria were seriously inhibited by THP-AD centrate, while long-term acclimation together with aeration optimization can mitigate such inhibition. A nitrogen removal rate (NRR) of 0.55 kg N/m 3 /d was obtained and maintained with 60% THP-AD centrate as feed. However, 100% THP-AD centrate caused sludge wash-out from PN reactor due to excessive polymer and high solids in influent. The alkalinity deficit also reduced the AOB activity. Moreover, anammox activity and overall NRR also declined (to 0.37 kg N/m 3 /d). The organics transformation mainly occurred in PN reactor with very low removal efficiency due to their recalcitrant characteristics. The humic acid-like, fulvic acid-like substances and building blocks were revealed as the major organic compounds in THP-AD centrate (51.5–53.8% TOC), which likely contributed to the recalcitrant. Nitrosomonas and Candidatus Brocadia were the major AOB and anammox bacteria in the PN and anammox reactors respectively. With the increased THP-AD centrate proportion in the feed, the abundance of both population declined. Interestingly, Denitratisoma, being the major denitrifying bacteria in anammox reactor, had relatively stable abundance (7.0–7.9%) when THP-AD centrate was improved from 3 and 100%, suggesting the inhibition on anammox bacteria was not due to the overgrowth of denitrifying microorganism despite the high organics loading rate. Overall, this study provides a guide to develop the energy-saving PN/A process for THP-AD centrate treatment by pointing out potential challenges and mitigating strategies.